2020
DOI: 10.1101/2020.08.06.240192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of papain-like protease from SARS-CoV-2 and its complexes with non-covalent inhibitors

Abstract: The number of new cases world-wide for the COVID-19 disease is increasing dramatically, while efforts to contain Severe Acute Respiratory Syndrome Coronavirus 2 is producing varied results in different countries. There are three key SARS-CoV-2 enzymes potentially targetable with antivirals: papain-like protease (PLpro), main protease (Mpro), and RNA-dependent RNA polymerase. Of these, PLpro is an especially attractive target because it plays an essential role in several viral replication processes, including c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(130 citation statements)
references
References 45 publications
3
127
0
Order By: Relevance
“…The substrate binding site in PLpro is made up of a canonical cysteine protease catalytic triad (Cys111, His272, and Asp286) (Fig. 1 ) found at the interface between the thumb and palm domains; other amino acids in the binding site are Trp106, Gly266, Gly271, His73, Arg140, and Asn109 [ 7 ]. The in silico docking of PLp with gallic acid derivatives revealed that 3-O-(6-galloylglucoside), 4-O-(6-galloylglucoside), and remdesivir had the utmost binding affinity scores of −6.6, −6.8, and −6.5 kcal/mol respectively (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The substrate binding site in PLpro is made up of a canonical cysteine protease catalytic triad (Cys111, His272, and Asp286) (Fig. 1 ) found at the interface between the thumb and palm domains; other amino acids in the binding site are Trp106, Gly266, Gly271, His73, Arg140, and Asn109 [ 7 ]. The in silico docking of PLp with gallic acid derivatives revealed that 3-O-(6-galloylglucoside), 4-O-(6-galloylglucoside), and remdesivir had the utmost binding affinity scores of −6.6, −6.8, and −6.5 kcal/mol respectively (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The substrate binding domain is made up of a canonical cysteine protease catalytic triad (Cys111, His272, and Asp286) (Fig. 1 ) found at the interface between the thumb and palm domains; other amino acids in these domain are Trp106, Gly266, Gly271, His73, Arg140, and Asn109 [ 7 ]. It is noteworthy that none of the hit compounds had interactions with the catalytic triad (Cys111, His272, and Asp286) and might be the reason for the characteristics BE values exhibited by them (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cleavage is mediated by two virally encoded proteases: the main viral protease, known as Mpro, 3CLpro or non-structural protein 5 (nsp5) and a second protease known as the papain-like protease, PLpro, a domain within nsp3 3 . There is much interest in developing de-novo inhibitors to target these proteases [5][6][7][8][9][10] but the full clinical development of such drugs is a time-consuming process, usually requiring several years.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the molecular docking results for 6WUU and the blind docking data, the receptor grid was adjusted for hypericin and its isomer. The residues that were used included K157, E167, D164, Y273, T301, Y264, P247, P248, Y268 and Q269 ( 52 , 96 ). In regards to 7JRN, the positive control compound GRL-0617 was docked using the QPLD protocol ( 90 , 91 , 92 , 93 , 94 , 95 ).…”
Section: Methodsmentioning
confidence: 99%